Emerson and environmental ethics - Dunston, Susan L. (Professor Emerita) (Lexington Books, 2018)
This book shows the Emersonian arc in environmental ethics and nature writing extending into contemporary discussions of those topics. Dunston connects Emerson's nature literacy and natural philosophy to contemporary forms of eco-feminism, living systems theory, Native American science, Asian philosophy, and environmental activism.